Enrollment in Florida's Institutions of Higher Learning Fall 1971 - Florida State Board of Regents, Tallahassee; Florida State Board of Regents, Tallahassee ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This document presents the enrollment figures for the institutions of higher education in Florida in the fall of 1971. The data are arranged in several categories: (1) statewide enrollment; (2) enrollment by institutions; (3) first time in college enrollment; (4) graduate student enrollment; and (4) trends and new developments in Florida higher education. The report reflects several trends of educational significance: the rapid growth of enrollment in the community colleges; the leveling off of lower division enrollment in the public universities; the increase in upper division enrollment in the State University System; and the steady, paced, collective enrollment gains of the institutions in the private sector. (Author/HS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Demand; Educational Supply; Enrollment; Enrollment Rate; Enrollment Trends; Higher Education; School Registration; Statistical Data